Changes in the gene expression profiles of the brains of male European eels (Anguilla anguilla) during sexual maturation - Churcher, Allison (2014)
Background: The vertebrate brain plays a critical role in the regulation of sexual maturation and reproduction by integrating environmental information with developmental and endocrine status. The European eel Anguilla anguilla is an important species in which to better understand the neuroendocrine factors that control reproduction because it is an endangered species, has a complex life cycle that includes two extreme long distance migrations with both freshwater and seawater stages and because it occupies a key position within the teleost phylogeny. At present, mature eels have never been caught in the wild and little is known about most aspects of reproduction in A. anguilla. The goal of this study was to identify genes that may be involved in sexual maturation in experimentally matured eels. For this, we used microarrays to compare the gene expression profiles of sexually mature to immature males. Results: Using a false discovery rate of 0.05, a total of 1,497 differentially expressed genes were identified. Of this set, 991 were expressed at higher levels in brains (forebrain and midbrain) of mature males while 506 were expressed at lower levels relative to brains of immature males. The set of up-regulated genes includes genes involved in neuroendocrine processes, cell-cell signaling, neurogenesis and development. Interestingly, while genes involved in immune system function were down-regulated in the brains of mature males, changes in the expression levels of several receptors and channels were observed suggesting that some rewiring is occurring in the brain at sexual maturity. Conclusions: This study shows that the brains of eels undergo major changes at the molecular level at sexual maturity that may include re-organization at the cellular level. Here, we have defined a set of genes that help to understand the molecular mechanisms controlling reproduction in eels. Some of these genes have previously described functions while many others have roles that have yet to be characterized in a reproductive context. Since most of the genes examined here have orthologs in other vertebrates, the results of this study will contribute to the body of knowledge concerning reproduction in vertebrates as well as to an improved understanding of eel biology.